2015
DOI: 10.1039/c5nr06144j
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional atomically thin MoS2nanosheets and their sensing applications

Abstract: The extraordinary properties of layered graphene and its successful applications in electronics, sensors, and energy devices have inspired and renewed interest in other two-dimensional (2D) layered materials. Particularly, a semiconducting analogue of graphene, molybdenum disulfide (MoS2), has attracted huge attention in the last few years. With efforts in exfoliation and synthetic techniques, atomically thin films of MoS2 (single- and few-layer) have been recently prepared and characterized. 2D MoS2 nanosheet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(107 citation statements)
references
References 115 publications
0
107
0
Order By: Relevance
“…It finds great application in flexible electronics due to its high stiffness and breaking strength [9]. MoS 2 has been successfully employed in energy harvesting, optoelectronics, lithium batteries, and sensing [10][11][12]. According to recent research, MoS 2 -based fluorescence biosensing systems exhibit better sensitivity than graphenebased methods [13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…It finds great application in flexible electronics due to its high stiffness and breaking strength [9]. MoS 2 has been successfully employed in energy harvesting, optoelectronics, lithium batteries, and sensing [10][11][12]. According to recent research, MoS 2 -based fluorescence biosensing systems exhibit better sensitivity than graphenebased methods [13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Single layer molybdenum disulfide (MoS 2 ) is one of the most widely investigated 2D materials, and possesses outstanding properties with applications in band gap engineering, optical and electrical devices, and spin-orbit research. 1,2 It has been reported that large-area and uniform single layer MoS 2 can be synthesized by performing chemical vapor deposition (CVD) on various substrates with atomically smooth surfaces such as SiO 2 on Si, sapphire, and mica. 3 However, the full exploitation of the potential of CVD MoS 2 requires a method for the clean transfer of the as-grown MoS 2 from the growth substrate to the target substrate without degeneration of its properties.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include micromechanical exfoliation, hydrothermal process, solution-based chemical exfoliation, chemical vaporization, ion intercalation exfoliation, and sulfurization of molybdenum (Mo)89101112. Exfoliated MoS 2 semiconductor has shown remarkable electrical properties and mechanical strength in various micro electronic device applications such as lasers13, supercapacitors14, thin film transistors (TFTs)15, phototransistors16, bio sensors17, solar cells18, and batteries19.…”
mentioning
confidence: 99%